Ancient Greek art - Hodge, Susie, 1960- (Des Plaines, Ill. : Heinemann Interactive Library, 1998)
Examines the art of ancient Greece, including mosaics, pottery, sculpture, architechture, and paintings
Includes bibliographical references (p. 31) and index
Keywords: Art, Greek -- Juvenile literature; Art, Ancient -- Greece -- Juvenile literature